A novel approach to estimate the distribution, density and at-sea risks of a centrally-placed mobile marine vertebrate. (May 2018) - Pikesley, Stephen K.; Agamboue, Pierre Didier; Bayet, Jean Pierre; Bibang, Jean Noel; Bonguno, Eric Augowet; Boussamba, François; Broderick, Annette C.; Coyne, Michael S.; Du Plessis, Philippe; Faure, François Edgard; Fay, J. Michael; Formia, Angela; et al.
Abstract: Formulating management strategies for mobile marine species is challenging, as knowledge is required of distribution, density, and overlap with putative threats. As a step towards assimilating knowledge, ecological niche models may identify likely suitable habitats for species, but lack the ability to enumerate species densities. Traditionally, this has been catered for by sightings-based distance sampling methods that may have practical and logistical limitations. Here we describe a novel method to estimate at-sea distribution and densities of a marine vertebrate, using historic aerial surveys of Gabonese leatherback turtle ( Dermochelys coriacea ) nesting beaches and satellite telemetry data of females at sea. We contextualise modelled patterns of distribution with putative threat layers of boat traffic, including fishing vessels and large ship movements, using Vessel Monitoring System (VMS) and Automatic Identification System (AIS) data. We identify key at-sea areas in which protection for inter-nesting leatherback turtles could be considered within the coastal zone of Gabonese Exclusive Economic Zone (EEZ). Our approach offers a holistic technique that merges multiple datasets and methodologies to build a deeper and insightful knowledge base with which to manage known activities at sea. As such, the methodologies presented in this study could be applied to other species of sea turtles for cumulative assessments; and with adaptation, may have utility in defining critical habitats for other central-place foragers such as pinnipeds, or sea bird species. Although our analysis focuses on a single species, we suggest that putative threats identified within this study (fisheries, seismic activity, general shipping) likely apply to other mobile marine vertebrates of conservation concern within Gabonese and central African coastal waters, such as olive ridley sea turtles ( Lepidochelys olivacea ), humpback dolphins ( Sousa teuszii ) and humpback whales ( Megaptera novaeangliae ). Highlights: At-sea distribution and densities of a marine vertebrate are modelled. Modelled patterns are contextualised with putative threat layers of vessel traffic. Key at-sea areas are identified where protective measures may be considered. This methodology may be adapted to describe critical habitats for other species.